The potential of employing artificial intelligence and neural networks in the physical training of aikido practitioners - Mikheev A.V.; Petrov P.K. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation of a mobile application for Aikido practitioners, utilizing artificial intelligence technologies, and assessing its potential for physical training. Methods and structure of the study. The academic and methodological literature on the application of artificial intelligence in Aikido, physical education, and sports is examined. A mobile application has been created using AI technology to tailor training programs to individual needs. A theoretical assessment of the potential efficacy of the developed application is conducted. Results and conclusions. The innovative mobile application has proven its ability to tailor training programs based on data analysis and user self-evaluation. Theoretical analysis has revealed that an application with artificial intelligence can adjust training loads, minimizing the risk of overtraining. The current version of the app has some drawbacks, such as a limited number of exercises. The next stage of development will involve adding automatic exercise counting using computer vision.